2019
DOI: 10.1101/736603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of amino acid and nucleotide metabolism by crustacean hyperglycemic hormone in the muscle and hepatopancreas of the crayfishProcambarus clarkii

Abstract: To comprehensively characterize the metabolic roles of crustacean hyperglycemic hormone (CHH), metabolites in two CHH target tissues of the crayfish Procambarus clarkii, whose levels were significantly different between CHH-silenced and saline-treated control animals, were analyzed using bioinformatics tools provided by an on-line analysis suite (MetaboAnalyst). Analysis with Metabolic Pathway Analysis (MetPA) indicated that in the muscle Glyoxylate and dicarboxylate metabolism, Nicotinate and nicotinamide met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The stimulatory effects of CHH on the release of amylase from the hepatopancreas ( 162 ) and hemolymph levels of triacylglycerols and phospholipids ( 163 ) have been reported but not further characterized. Recently, the metabolic roles of CHH in the crayfish P. clarkii were more comprehensively characterized using an RNAi approach (double-stranded RNA) followed by profiling the hepatopancreas and muscle metabolomes ( 77 , 78 ). The combined data indicated that CHH has more diverse effects than previously realized, and the two target tissues are differentially regulated.…”
Section: Biological Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stimulatory effects of CHH on the release of amylase from the hepatopancreas ( 162 ) and hemolymph levels of triacylglycerols and phospholipids ( 163 ) have been reported but not further characterized. Recently, the metabolic roles of CHH in the crayfish P. clarkii were more comprehensively characterized using an RNAi approach (double-stranded RNA) followed by profiling the hepatopancreas and muscle metabolomes ( 77 , 78 ). The combined data indicated that CHH has more diverse effects than previously realized, and the two target tissues are differentially regulated.…”
Section: Biological Functionsmentioning
confidence: 99%
“…The combined data indicated that CHH has more diverse effects than previously realized, and the two target tissues are differentially regulated. The main effects of CHH are stimulation of glycolysis and lipolysis in the hepatopancreas, and higher rate of utilization of carbohydrates (glucose and other sugars, including fructose, galactose, sucrose, and lactose) via glycolysis and TCA cycle (resulting in higher levels of ATP), stimulation of the pentose phosphate pathway (PPP) flux (leading to increased levels of nucleotide biosynthesis), and elevation of amino acid biosynthesis in the muscle ( 77 , 78 ). Stimulation of the “Nicotinate and nicotinamide metabolism”, which concerns the metabolism of two nicotinamide coenzymes (NAD + and NADP + ), is central to the metabolic effects of CHH in the muscle.…”
Section: Biological Functionsmentioning
confidence: 99%
See 3 more Smart Citations